Audiological findings in a case of von rccklinghauscn’s multiple neurofibromatosis - M.N. Nagaraja, KM. Chandrashekar, Joan D’Mello (Journal of All India Institute of Speech and Hearing)
Bilateral acoustic tumors are reported to be the most common intracranial tumor in adults with von Recklinghauseris disease. The audiological lest findings are reported to be confounded in the presence of bilateral acoustic neurenomas. There)rore, the audiological findings has tobe interpreted vvilh great care. The report of such a confounded audiological test finding in a case of von Recklinghausen’ s disease is discussed in this paper.